EFFECTS OF TWO DIFFERENT DOSAGE OF BCAA SUPPLEMENTATION ON SERUM INDICES OF MUSCLE DAMAGE AND SORENESS IN SOCCER PLAYERS - Payam Mohamad-Panahi; Soran Aminiaghdam; Navid Lotfi; Khaidan Hatami (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The purpose of this study was to investigation of the effects of two different dose of BCAA supplementation on serum indices of muscle damage and soreness in soccer players. 30 male soccer players (age: 20.2+-0.6 yr) participated as subjects in this study. Subjects were randomly divided into three groups (double-blind design). All subjects performed lower- body resistance exercise (6 sets, 10 repetitions, 70% 1RM). The BCAA was given at doses of 200 and 450 mg.kg -1 BW for supplemental groups 1 and 2, respectively, 30 minutes before and after to exercise tests and carbohydrate was given at dose of 200 mg.kg -1 BW for placebo group. To identify enzymes activity (IU/L), venous blood samples were collected 30 min prior to exercise and at 24 and 48 hrs post exercise. Data were statistically analyzed using repeated measures ANOVA and Bonfferoni test. Baseline CK, CK-MB and muscle soreness were determined 30 minutes before the exercise test. Baseline serum values for CK, CK-MB and baseline muscle soreness were not different between groups in the 30 minutes before the exercise test (p>0/05). However, there were significant increases between the pre-exercise and post-exercise values for CK, CK-MB and muscle soreness from 24 hrs to 48 hrs post-test (p<0/05), but there were no significant differences between two groups (p< 0.05(. These results suggested that two different dosages of BCAA supplementation did not affect muscle damage and muscle sureness during resistance exercise bout in soccer players.